PENGARUH GEL KOMBINASI EKSTRAK JINTAN HITAM (Nigella sativa L.) DAN KULIT MANGGIS (Garcinia mangostana L.) TERHADAP ANGIOGENESIS PENYEMBUHAN LUKA ULKUS TRAUMATIKUS PADA TIKUS WISTAR (Rattus norvegicus) - Gunawan, Isabella Avrilia; Dr. drg. Nur Permatasari, MS. (E-Prodenta Journal of Dentistry, 2025)
Traumatic ulcers are traumatic wounds that occur on the oral mucosa resulting in loss of surface epithelium. The process of healing ulcers involves angiogenesis, which is the formation of new blood vessels. Treatment of traumatic ulcers uses Triamcinolone acetonide, but it has side effects so alternative medicines are needed with antiinflammatory herbal plants, namely black cumin and mangosteen peel which have been proven to speed up wound healing. The aim of this study was to determine the effect of a combination gel of black cumin extract (Nigella sativa L.) and mangosteen peel (Garcinia mangostana L.) on angiogenesis of traumatic ulcer wound healing in wistar rats (Rattus norvegicus). This research method uses a Randomized Post Test Only Controlled Group Design in vivo with 40 male Wistar rats, divided into groups are negative control (K-), positive control (K+), and treatments (P1, P2, P3) with two time series. Samples were obtained from the traumatic ulcer area on the labial mucosa of the lower jaw of wistar rats, then HE stained and observed with a light microscope with a magnification of 400 times. The gel treatment group with a combination of black cumin extract (Nigella sativa L.) and mangosteen peel (Garcinia mangostana L.) showed a higher average number of blood vessels and has the potential for a faster healing process for traumatic ulcers than the other groups. The results of the research can be concluded that the combination gel of black cumin extract (Nigella sativa L.) and mangosteen peel (Garcinia mangostana L.) has an effect on angiogenesis in healing traumatic ulcer wounds in Wistar rats (Rattus norvegicus).